Consumption and oviposition rates of six phytoseiid species feeding on eggs of the cassava green mite Mononychellus tanajoa (Acari: Tetranychidae) - Cuéllar Jimenez, M.E.; Calatayud, Paul-André; Melo Molina, E.L.; Smith, L.; Bellotti, Anthony C. (2001)
In Africa the cassava green mite, Mononychellus tanajoa, is an important pest of cassava, Manihot esculenta. Phytoseiid mites from South America are being evaluated as potential biological control agents of this alien pest. We evaluated six phytoseiid (Acari: Phytoseiidae) species, collected in South America: Euseius ho, Typhlodromalus aripo, Typhlodromalus tenuiscutus, Neoseiulus californicus, Neoseiulus idaeus, and Galendromus annectens. Their effectiveness as a biological control agent was estimated by measuring rates of prey consumption and oviposition in relation to prey density under optimal laboratory conditions. Prey consumption by E. ho, T. aripo and T. tenuiscutus continued increasing linearly up to the highest density of prey evaluated (200 prey eggs) for a maximum of 93, 101 and 59 prey in 24 h. For the other predators, prey consumption levelled off at prey density of 30 or more. Maximum daily consumption was 40, 35 and 18 eggs for N. californicus, N. idaeus and G. annectens, respectively. Except for T. tenuiscutus, daily fecundity appeared to reach a plateau at the prey densities tested. Higher maximum daily oviposition rates were registered for T. tenuiscutus, N. californicus, N. idaeus and G. annectens, ovipositing 3.9, 3.6, 2.9 and 2.8 eggs, respectively; whereas E. ho and T. aripo oviposited a maximum of 2.2 and 1.4 eggs in 24 h, respectively. The ratio between oviposition and prey consumption rates was generally higher for G. annectens, N. californicus and N. idaeus. The high prey consumption rate of E. ho, T. aripo and T. tenuiscutus suggests that these species are the best agents in regard to the attack of pest eggs. The high fecundity rate and oviposition/consumption ratio especially at low prey densities (30 prey eggs) of N. californicus, N. idaeus and G. annectens suggests that these species may be able to multiply well at low prey densities.